(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The dynamic market environment causes constant updating and increasing the amount of information, which is especially important for the process of strategic choice of the enterprise. This requires the use of information systems that support strategic choice. The purpose of the article is to consider the dynamics of approaches to strategic management and their provision of information systems, and to explore the features of modern aspects of the use of information systems and technologies of enterprises to improve the effectiveness of strategic choice. It is substantiated that the implementation of information systems is associated with the complexity of configuration, configuration and updating, the complexity of their implementation, often forced to change the way of functioning through technical, IT, cultural, restructuring and organizational aspects, as well as business features. Knowledge is important. as on the part of the enterprise where the systems are installed, software vendors, implementation teams and related services of implementation methods related to specific systems. Based on the analysis of scientific achievements of world and Ukrainian scientists of information management systems, the classification of information systems that support strategic choice in the enterprise is proposed. The proposed division takes into account the nature of the strategic selection process and the possible amount of information support for management information systems and can be used by enterprises to determine opportunities for future development. It is established that the changes taking place in the perception of strategic orientation of enterprises and IT systems for management needs. It is proved that the assessment of information technology prospects allows to form a correct real assessment of new capabilities of the organization in order to increase its competitiveness through the introduction of information technology, consider ways to change relations with consumers, suppliers, develop strategies for implementing specific information technologies. in general, justify the necessary measures to maintain a given level of reliability in specific areas of activity in the use of information technology, develop their own plan for the implementation of the required information technology, taking into account the reaction of the environment and, in particular, competitors.